1993
DOI: 10.1002/jnr.490360412
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the human MBP promoter in primary cultures of oligodendrocytes: Positive and negative cis‐acting elements in the proximal MBP promoter mediate oligodendrocyte‐specific expression of MBP

Abstract: Since the regulation of myelin basic protein expression depends primarily on the initiation of transcription, we analyzed the 5' flanking region of the human myelin basic protein gene in transient transfection studies in primary cultures of developing oligodendrocytes. We demonstrated that 149 base pairs 5' of the initiation of transcription was sufficient to direct oligodendrocyte-specific expression of myelin basic protein. The capsite of the fusion transcript was identical with that of the endogenous myelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…Several laboratories have demonstrated that relatively small regions of DNA sequence upstream of both the PL P and M BP genes are sufficient for developmental and tissue-specific activation of lacZ expression in oligodendrocytes in transgenic animals (Gow et al, 1992;Goujet-Z alc et al, 1993;Wright et al, 1993;Wrabetz et al, 1995), and transcription factors interacting with these regions have been identified (Berndt et al, 1992;K im and Hudson, 1992;Haas et al, 1993;Wrabetz et al, 1993). Only one of these factors, MyT1, a member of the zinc finger family of DNA-binding proteins, has been shown to be expressed in oligodendrocytes (Armstrong et al, 1995).…”
mentioning
confidence: 99%
“…Several laboratories have demonstrated that relatively small regions of DNA sequence upstream of both the PL P and M BP genes are sufficient for developmental and tissue-specific activation of lacZ expression in oligodendrocytes in transgenic animals (Gow et al, 1992;Goujet-Z alc et al, 1993;Wright et al, 1993;Wrabetz et al, 1995), and transcription factors interacting with these regions have been identified (Berndt et al, 1992;K im and Hudson, 1992;Haas et al, 1993;Wrabetz et al, 1993). Only one of these factors, MyT1, a member of the zinc finger family of DNA-binding proteins, has been shown to be expressed in oligodendrocytes (Armstrong et al, 1995).…”
mentioning
confidence: 99%
“…In addition, we showed by transient transfection analysis in primary cultures of oligodendrocytes that 750, 420, or 149 nt of human MBP promoter was sufficient to activate a 5-10-fold increase in the expression of the CAT reporter gene in oligodendrocytes, but not in other cell types (12). We also showed that the 149-nt region contained two subregions with opposing functional activities: (a) the proximal 102-nt region activated the expression of CAT in most cell types; and (b) the more distal region, from Ϫ149 to Ϫ102 nt, silenced the expression of CAT in them.…”
Section: Myelin Basic Protein (Mbp)mentioning
confidence: 94%
“…Plasmids--All deletions of the proximal 149-nt MBP promoter were prepared by a modification of the exonuclease III/mung bean nuclease technique (Stratagene), as described previously (12). Transversion mutations spanning from 149 to 110 nt of the MBP promoter were prepared by polymerase chain reaction-mediated mutagenesis, as described previously (12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations